Relacionamento entre compartilhamento do conhecimento, capacidade absortiva e performance em times ágeis - Balle, Andrea Raymundo (2019)
Knowledge sharing is a process where units influence each other through their experiences. It is related to the absorptive capacity, a skill that allows the company to identify external knowledge, to assimilate and to apply it for commercial purposes. Several factors influence both knowledge sharing and absorptive capacity, including goal orientations, a concept that proposes two objectives in situations of achievements related to tasks: learning or performance. An organizational context that is linked to knowledge sharing, enables the absorptive capacity and encourages learning and performance is software development. Software development is a globalized phenomenon and therefore is important to study the national culture in which the development is taking place. Based on that, this work investigates the relationship between the inter-team knowledge sharing, the absorptive capacity of the teams and the goal orientations in the context of software development teams in Brazil and Portugal. To reach this objective, the research was developed with a systematic literature review and with two phases of empirical research: a quantitative phase, using a survey to verify the research model, and a qualitative phase, in order to explain the results obtained in the quantitative phase. Results from the quantitative phase (1) confirm the influence of the goal orientations in knowledge sharing and absorptive capacity and the influence of absorptive capacity in the knowledge sharing in an intercalated manner, considering the concepts as more than one construct; and (2) show there are differences in some model relationships in different countries and methodologies. Qualitative phase results show that (1) the non-confirmation of hypotheses in the complete model occurs due to problems in the knowledge flow, due to the over-focus on tacit knowledge and the importance of the potential absorptive capacity; and (2) the differences in outcomes between groups depend on the maturity of industry and methodology in the country, and also on the cultural dimensions of masculinity x femininity, uncertainty avoindance, power distance, restriction x indulgence, and short-term x long-term. As academic implications, the work clarifies the relationship between absorptive capacity and knowledge sharing, reinforces the robustness of potential and realized absorptive capacity, and shows the importance of cultural dimensions in software development teams. For managers, this work helps to understand team behavior and serves as a guidebook for leveraging the absorptive capacity and knowledge sharing, guided by cultural dimensions and how they explain relationships.